When the Teacher Is the Test Proctor - Childs, Ruth; Umezawa, Linda (Canadian Journal of Education/Revue canadienne de l’éducation, 2009)
This study investigates what grade‐3 teachers say they would do if faced with common test administration dilemmas – and why. Grade‐3 teachers with experience administering On‐ tario’s provincially mandated assessment were recruited through professional association newsletters and Toronto‐area newspapers. They responded to an on‐line questionnaire (n = 98) or an hour‐long interview (n = 40). Many teachers predicted that they would not follow the test administration instructions. Their rationales included (a) supporting the students to do their best work, (b) ensuring a positive testing experience for the students, and (c) main‐ taining their pedagogical routines and their relationships with the students. The findings highlight the ethical dilemmas teachers may experience when proctoring tests. Key words: large‐scale assessment, standardized testing, test administration, Ontario edu‐ cation Les auteures analysent ce que des enseignants de 3e année feraient selon eux s’ils étaient confrontés avec les dilemmes courants reliés à l’administration de tests et les raisons pour lesquelles ils agiraient ainsi. Des enseignants de 3e année habitués à faire passer des tests provinciaux en Ontario ont été recrutés par le biais d’annonces dans des bulletins d’associations professionnelles et des journaux de la région de Toronto. Ils ont répondu à un questionnaire en ligne (n = 98) ou participé à une entrevue d’une heure (n = 40) ; près de 80 % des enseignants dans les deux groupes provenaient de la Région du Grand Toronto. De nombreux enseignants ont indiqué qu’ils ne suivraient pas les directives au sujet de l’administration des tests parce qu’ils veulent, entre autres : (a) aider les élèves à faire de leur mieux, (b) faire en sorte que les élèves aient une expérience positive des tests et (c) suivre leurs méthodes pédagogiques habituelles et conserver leurs liens avec les élèves. Les conclusions des auteures mettent en évidence les dilemmes éthiques auxquels les ensei‐ gnants peuvent faire face lorsqu’ils surveillent l’administration de tests. Mots clés : tests communs, tests normalisés, administration de tests, éducation en Ontario.